Debt Management Performance Assessment Tool - World Bank (Washington, DC, 2013)
The World Bank is developing a program to assist developing countries improve debt management in collaboration with other partners. The objective of the program is to help strengthen capacity and institutions in developing countries to manage government debt in an effective and sustainable manner in the medium to long term. A cornerstone of the program is the Debt Management Performance Assessment Tool (DeMPA), a methodology for assessing performance through a comprehensive set of performance indicators spanning the full range of government debt management (DeM) functions. The intention is that the indicator set will be an internationally recognized standard in the government debt management field and may be applied in all developing countries. The DeMPA highlights strengths and weaknesses in government DeM practices in each country. Performance assessment facilitates the design of plans to build and augment capacity and institutions tailored to the specific needs of a country. The debt management performance report will not, however, contain specific recommendations or make assumptions as to the potential impact of ongoing reforms on government DeM performance. The DeMPA also facilitates the monitoring of progress over time in achieving the objectives of government DeM consistent with international sound practice. [Revised November 2008]